Eficiencia en la ejecución presupuestal y la aceptación de la gestión del Gobierno Regional de Loreto 2011-2022 - Ramírez Reátegui, Daniel Elías (2024)
Both authorities and the general citizenry express a pronounced interest in matters related to the public budget and management. This is because effective management of public resources is crucial for achieving comprehensive socioeconomic development of society as a whole. The research was quantitative in nature, at a descriptive-correlational level, and employed a non-experimental design with longitudinal data. This approach provides a quantitative tool that allows for the assessment of whether the decisions made have the support of the population or if, conversely, there are levels of dissatisfaction that require the adoption of appropriate measures to prevent an increase in discontentment with public management. After conducting inferential statistical analysis, it was determined that there is no significant relationship between the efficiency variables in budget execution and the approval of the management of the Regional Government of Loreto during the period 2011-2022; otherwise, there is a strong direct relationship of 71.89% between the efficiency in budget execution in education, culture, and sports with a lag period, and the approval of the management of the Regional Government of Loreto 2011-2022, making it the only budgetary matter that shows a real association with the evolution of the second observed variable.